(untitled) (The Journal of Plant Protection Sciences, 2021)
Termitidae is the largest family of termites. The workers of the subfamily Macrotermitinae have the extra-ordinary phenomena of making fungus combs inside the termitophiles. Considering the consistency of fungus-bed in the termitophiles, an attempt has been made to observe the morphological changes of nymphs while they stayed within the fungus comb. Biological attributes indicated that Odontotermes proformosanus are polymorphic in nature and have exopterygote post-metamorphic development. During the period of study, eggs and nymphs were collected in different seasons from the fungus combs of termite mounds. Eggs of O. proformosanus were found profusely in fungus comb in the months of March, May, September and October of 2006 to 2008 Average lengths and standard deviation (mean±SD) of the eggs were (0.66 ± 0.09), width (0.04 ± 0.07) mm and egg shape ratio is 0.53. Eggs were mostly of broad type. st th st Distinct quiescent period was also observed. Morphological changes completed within 1 to 5 stages. In the 1 stage, th total length ranged from 0.8-1.5 mm. Terminal form of workers and soldiers were attained at the 5 stage (4.1- 4.5 mm in body length). During the period of observation, it was found that total length of the nymph, head length and head capsule width are significantly correlated at 0.01 level in their five different development stages.